Preparation of nanostructured goethite by chemical precipitation in a rotating packed bed. Issue 2 (15th January 2023) - Lin, Chia-Chang; Lin, Jun-Hong; Wu, Kuan-Yi
Abstract: Nanostructured goethite was successfully prepared at 25°C by chemical precipitation in the rotating packed bed in which the rotational speed was 1800 rpm, the flow rate of aqueous FeCl3 with a concentration of 0.3 mol/L was 0.5 L/min, and the flow rate of aqueous NaOH with a concentration of 0.9 mol/L was 0.5 L/min. The prepared nanostructured goethite had an average crystallite size of 20 nm and a needle shape with a mean length of 500 nm. Moreover, the prepared nanostructured goethite exhibited the Type-III isotherm for N2 adsorption-desorption with a BET specific surface area of 23 m 2 /g. The rotating packed bed with the chemical precipitation approach yielded a rate of preparation of nanostructured goethite of about 19 kg/day. The adsorption capacity of the prepared nanostructured goethite was examined using the adsorption of dyes in water. Based on the Langmuir model, its maximum adsorption capacity for Reactive Red 2 was 29.1 mg/g, and its maximum adsorption capacity for Orange G was 24.5 mg/g. Accordingly, the prepared nanostructured goethite can be used as a potential adsorbent for removing dyes from water.